Evidence-Based Guidance for One Health Preparedness, Prevention, and Response Strategies to Marburg Virus Disease Outbreaks - Claude Mambo Muvunyi; Jean Claude Semuto Ngabonziza; Noella Bigirimana; Nicaise Ndembi; Emmanuel Edwar Siddig; Jean Kaseya; Ayman Ahmed (Diseases)
Objectives: Marburg virus disease (MVD) is on the WHO list for pandemic-prone pathogens. The current outbreak in Rwanda provides an opportunity to map outbreaks and generate information to inform policymaking, resource mobilization, and guide the implementation of cost-effective response strategies. Methods: We synthesized available information about MVD to build holistic, up-to-date evidence to inform policymakers, public health leaders, and healthcare and public health services providers in their development and implementation of cost-effective preparedness, prevention, and control measures. Results: We have identified 20 outbreaks of MVD that occurred in 14 countries between 1967 and 2024; these outbreaks led to 580 confirmed cases and 423 deaths in total. We summarize the available information about the main clinical signs, diagnostic tools, primary reservoir, transmission dynamics, and case management protocol. We also document the best practices in the prevention and control of MVD outbreaks, including the implementation of a multisectoral One Health strategy for preparedness, prevention, and response to MVD outbreaks that incorporates the strict implementation of WASH and infection prevention measures, contact tracing, and the isolation of infected and suspected humans and animals, and enhances the implementation of the International Health Regulations, particularly efficient cross-country coordination. Conclusions: In the absence of a licensed treatment or vaccine for MVD, the response strategy to MVD should focus on preventive measures, including community engagement to promote the reduction in contact between humans and reservoirs, the supportive care and isolation of patients, and proper waste management. High risk populations such as frontline responders, including healthcare providers and community health workers, should be prioritized so that they can access all currently available protection measures.